The Impact of Electronic Payment Systems of the Financial Perofrmance of Small and Medium Enterprises in Bidrendranagar, Surkhet - Thapa, Ashish (Journal of Entrepreneurship & Management Studies, 2025)
This study examines how the adoption of Electronic Payment Systems (EPS) influences the financial performance (FP) of Small and Medium Enterprises (SMEs) in Birendranagar, Surkhet, Nepal. The main objective is to assess the relationship between EPS usage and financial outcomes, considering factors like firm size and sectoral diversity. Adopting a quantitative research approach, the study combines descriptive and causal research designs to analyze both the current patterns of EPS use and its financial implications. Data were collected through structured questionnaires administered to a convenience sample of 150 SMEs operating in the retail, service, and manufacturing sectors. Descriptive statistics were used to outline EPS adoption trends, while correlation and regression analyses tested the hypothesized relationships using SPSS version 20. The findings reveal a significant positive relationship between EPS adoption and financial performance, with firm size also contributing to improved fiscal outcomes. SMEs using EPS experienced better revenue growth, operational efficiency, and transaction transparency. The study concludes that EPS adoption plays a vital role in strengthening the financial performance of SMEs in semi-urban areas like Birendranagar. It recommends that financial institutions and policymakers promote digital payment solutions tailored to the local business environment, facilitating broader EPS access and awareness to support SME growth and regional economic development.